2006
DOI: 10.1002/jcp.20909
|View full text |Cite
|
Sign up to set email alerts
|

ERK1/2‐driven and MKP‐mediated inhibition of EGF‐induced ERK5 signaling in human proximal tubular cells

Abstract: The MEK1-ERK1/2 signaling pathway has been implicated in the regulation of renal epithelial cell proliferation, epithelial-to-mesenchymal transition and the induction of an invasive cell phenotype. Much less information is available about the MEK5-ERK5 module and its role in renal epithelial cell proliferation and differentiation. In the present study we have investigated the regulation of these two families of extracellular signal-regulated kinases in epidermal growth factor (EGF)-stimulated human kidney-2 (H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 49 publications
1
25
1
Order By: Relevance
“…With respect to HK-2 cell proliferation, both EGF and BPE have been reported to act as essential mitogens for these cells (46,47). However, in the present study we observed that HK-2 cells proliferate even in the absence of growth supplements such as FBS, recombinant EGF or BPE (Fig.…”
Section: Osm-induced Expression Of Collagen Type I and Vimentin In Hkcontrasting
confidence: 54%
See 1 more Smart Citation
“…With respect to HK-2 cell proliferation, both EGF and BPE have been reported to act as essential mitogens for these cells (46,47). However, in the present study we observed that HK-2 cells proliferate even in the absence of growth supplements such as FBS, recombinant EGF or BPE (Fig.…”
Section: Osm-induced Expression Of Collagen Type I and Vimentin In Hkcontrasting
confidence: 54%
“…Human kidney 2 (HK-2) cells were cultured in keratinocyte-serum-free medium (KSFM) containing 10% FBS, 5 ng/ml recombinant epidermal growth factor (rEGF), 0.05 mg/ml BPE, 100 U/ml penicillin, and 100 g/ml streptomycin (46,47). The cells were grown at 37°C in a humidified 5% CO 2 atmosphere and split at a 1:5 ratio once a week.…”
Section: Methodsmentioning
confidence: 99%
“…[8][9][10] The cells (passages [20][21][22][23][24][25][26][27][28][29][30] were grown at 371C in a humidified 5% CO 2 atmosphere, and split at a 1:10 ratio, once a week. After growth to a subconfluent state, cells were washed once, made quiescent by incubation in serum-and supplementfree medium for 48 h, and then used for experiments.…”
Section: Cell Culturementioning
confidence: 99%
“…9 RNA quantity was estimated by spectrophotometric analysis. Reverse transcription was carried out in 20 ml volume using 2 mg total RNA, 1 mM random hexanucleotides as primer (Roche Diagnostics, Indianapolis, IN, USA), and Omniscript Reverse Transcriptase (Qiagen) according to the manufacturer's instructions.…”
Section: Rna Isolation and Real-time Pcr Analysismentioning
confidence: 99%
See 1 more Smart Citation